2011
DOI: 10.1074/jbc.m111.261321
|View full text |Cite
|
Sign up to set email alerts
|

Hsc70 Protein Interaction with Soluble and Fibrillar α-Synuclein

Abstract: The aggregation of ␣-synuclein (␣-Syn), the primary component of Lewy bodies, into high molecular weight assemblies is strongly associated with Parkinson disease. This event is believed to result from a conformational change within native ␣-Syn. Molecular chaperones exert critical housekeeping functions in vivo including refolding, maintaining in a soluble state, and/or pacifying protein aggregates. The influence of the stressinduced heat shock protein 70 (Hsp70) on ␣-Syn aggregation has been notably investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
93
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 42 publications
10
93
0
1
Order By: Relevance
“…This is why cross-linking was performed in the absence of nucleotide. No inhibition ␣-Syn assembly is observed in the presence of ADP (18). Consistent with that no Hsc70-␣-Syn complex with apparent molecular mass of 100 kDa was observed in the presence of BS2G and ADP.…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…This is why cross-linking was performed in the absence of nucleotide. No inhibition ␣-Syn assembly is observed in the presence of ADP (18). Consistent with that no Hsc70-␣-Syn complex with apparent molecular mass of 100 kDa was observed in the presence of BS2G and ADP.…”
Section: Resultssupporting
confidence: 68%
“…Interaction between Hsc70 and Soluble ␣-Syn-We recently demonstrated that Hsc70 sequesters ␣-Syn in an assembly incompetent state (18). We show here (Fig.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations